استخدام تقنيات الذكاء الاصطناعي والتزييف العميق للمعلومات: دراسة مسحية على مدى ممارسة الإعلاميين السودانيين للتطبيقات الرقمية في كشف المحتوى الزائف لشبكات التواصل الاجتماعي - حمدالله، شذى حمدالله محجوب (جامعة أم درمان الأهلية - كلية الآداب, 2024)
استخدمت تقنيات الذكاء الاصطناعي في السنوات الأخيرة في مجالات متباينة، وأثرت على محتوى كثير من التطبيقات المستخدمة على شبكة الإنترنت، ومن ضمنها شبكات التواصل الاجتماعي، التي أصبح محتواها ذو أثر كبير على الحياة اليومية، ومثل ما لهذه التقنيات من استخدام إيجابي، لها كذلك استخدام سلبي مؤثر على المحتوى المنشور، مثل إنشاء مقاطع الصوت والفيديو غير الحقيقية، وهو ما يعرف بالتزييف العميق "Deep fakes"، وبالتالي يؤثر هذا المحتوى المزيف على المجتمع ويتضرر أفراده بانتشار الشائعات، والتأثير على الرأي العام بمحتوى مزيف له أبعاد مختلفة. رأت الباحثة أن تدرس أثر تقنيات الذكاء الاصطناعي في التزييف العميق للمحتوى المنشور على مواقع التواصل الاجتماعي، ومعرفة وجهة نظر الإعلاميين السودانيين في استخدام الأدوات الرقمية والمبادرات العربية في تنقية المحتوى المزيف وتحري الدقة وبيان الحقائق. استخدمت الباحثة المنهج الوصفي المسحي بما يتوافق مع متطلبات الدراسة، ومن أهم النتائج التي توصلت لها أن استخدام الإعلاميون السودانيون للأدوات الرقمية والمبادرات العربية، ذو أثر إحصائي واضح على تنقية المحتوى المزيف على شبكات التواصل الاجتماعي. ومن أسباب انتشار المحتوى المزيف الصمت الإعلامي وعدم وجود قانون رادع يؤثر على التقليل من انتشار هذا المحتوى. ومن أهم التوصيات أهمية تنظيم ونشر استخدام الأدوات الرقمية لمحاربة التزييف العميق، وتطوير مبادرة سودانية لكشف التزييف أسوة بالمبادرات العربية الأخرى. Artificial intelligence techniques have been used in recent years in various fields, and have affected the content on many applications used on the Internet; including social networking sites, which have content that has had a great impact on daily life. While these technologies have positive uses, they also have negative ones that impact published content. An example of that is the creation of fake audio and video clips, which are known as “deep fakes”, and thus this fake content affects society and harms its members by the spread of rumors. Moreover, the public opinion can be influenced by such fake content. The researcher decided to study the impact of artificial intelligence techniques on the deep faking of the content published on social networking sites, and to know the point of view of Sudanese media professionals by using digital tools and Arab initiatives to filter out fake content, investigate the accuracy, and state the facts. The researcher used the descriptive survey method in accordance with the requirements of the study, and one its most important findings is that the Sudanese media professionals’ use of digital tools and Arab initiatives have had a clear statistical impact on the purification of fake content on social networking sites. One of the causes of the wide spread of fake content is the lack of media coverage as well as the lack of a deterrent law that could help in reducing the spread of this content. Among some of the most important recommendations is the organizing the use of digital tools and making it more common to combat deep faking, and allocating and developing a Sudanese initiative to detect counterfeits, similar to other Arab initiatives.
Keywords: الذكاء الاصطناعي -- المحتويات الزائفة -- الشبكات الاجتماعية -- السودان